Crystal structure of 2RS,5-diphenyl-8RS-3,5,7-triazatricyclo[6.5.1.0 3,7]-tetradeca-9,11,13-triene-4,6-dione, C23H 19N3O2 - Gream, G.E. (2014)
Zeitschrift fur Kristallographie - New Crystal Structures